2012
DOI: 10.1186/1752-0509-6-s2-s14
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 3' end nucleotide modification patterns and arm selection preference in liver tissues

Abstract: BackgroundThe expression of microRNA (miRNA) genes undergoes several maturation steps. Recent studies brought new insights into the maturation process, but also raised debates on the maturation mechanism. To understand the mechanism better, we downloaded small RNA sequence reads from NCBI SRA and quantified the expression profiles of miRNAs in normal and tumor liver tissues.ResultsFrom these miRNA expression profiles, we studied several issues related to miRNA biogenesis. First of all, the 3' ends of mature mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 34 publications
6
44
0
Order By: Relevance
“…For example, miRNA 3′ uridylation and adenylation exhibit sequence specificity—some miRNAs are predominantly adenylated while others are predominantly uridylated [79,88]. This is consistent with the fact that some nucleotidyl transferases (such as Arabidopsis URT1 and HESO1 and Drosophila Tailor) exhibit a preference for the 3′ nucleotide in its substrate RNA [55,72,73] (Table 1 and Figure 2).…”
Section: Specificity and Regulation Of Rna Uridylation And Adenylationsupporting
confidence: 58%
See 2 more Smart Citations
“…For example, miRNA 3′ uridylation and adenylation exhibit sequence specificity—some miRNAs are predominantly adenylated while others are predominantly uridylated [79,88]. This is consistent with the fact that some nucleotidyl transferases (such as Arabidopsis URT1 and HESO1 and Drosophila Tailor) exhibit a preference for the 3′ nucleotide in its substrate RNA [55,72,73] (Table 1 and Figure 2).…”
Section: Specificity and Regulation Of Rna Uridylation And Adenylationsupporting
confidence: 58%
“…In GLD2 knockout mice, miR-122 levels were selectively reduced, suggesting that 3′ adenylation stabilizes the miRNA [77]. In human fibroblasts, miR-122 is also monoadenylated and stabilized by GLD2 [78], and the hepatitis B virus may inhibit the process of miR-122 adenylation [79]. Adenylation of miRNAs may have a widespread functional impact in humans, because miRNAs in a variety of human cells are modified by adenylation [77,78,80,81].…”
Section: 3′ Adenylation Affects Rna Synthesis and Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, the arm selection change seems to be attributable to the thermodynamic properties of the miR–miR* duplex. However, numerous studies have reported that the miR#-5p/miR#-3p ratio varies among cell types or during carcinogenesis; therefore, the thermodynamic model alone is insufficient to explain the arm selection change68910111431. Recently, the concept of target-mediated miRNA protection (TMMP) was proposed by Chatterjee et al 31…”
Section: Resultsmentioning
confidence: 99%
“…This dominant miRNA is typically known as mature miRNA. Nonetheless, the extensive use of next generation sequencing revealed that the dominant arm can differ in different tissues and developmental times678910 in a process called arm switching11. The dominant miRNA is incorporated to RNA-induced silencing complex (RISC) and direct regulation of target-genes through the action of Argonaute (AGO) protein12.…”
mentioning
confidence: 99%